Viability assessment of small-scale on-grid wind energy generator for households in Malaysia - Alkawsi G.; Baashar Y.; Alkahtani A.A.; Lim C.W.; Tiong S.K.; Khudari M. (MDPI AG, 2023)
Cost benefit analysis; Electric power plants; Wind; Wind power; Wind turbines; Electrical power generation; Financial evaluation; Financial profits; Government supports; Hybrid optimization; Renewable projects; Small scale wind turbines; Wind energy generators; Microgrids